(untitled) (Journal of Chemical Engineering, 2017)
The basic objective of this paper has been to carry out comparative cost analyses for popularizing Liquefied Petroleum Gas (LPG) as a commensurate alternative to piped natural gas for domestic use in Bangladesh. Costing of LPG in three alternative scenarios of LPG utilization-LPG in cylinder, LPG supply in pipeline network for certain area and LPG in reticulated system-have been studied. Pricing of LPG and piped natural gas for domestic use have also been studied so as to recommend cross-subsidy option in LPG pricing that involves raising the price of natural gas for domestic use in order to finance LPG for expected lowering of its price, thus ensuring its access to the common people of the country. Reticulated LPG option, a semi-automatic system, has been found to be suitable as an alternative to piped natural gas for domestic use in terms of cost, flexibility and safety consideration. Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 16-20